Бельчонок Тишка: [сказка] / [Ирина Валерьевна Гурина] - Гурина Ирина Валерьевна (Фламинго, 2016)
Автор указан перед выходными данными Экземпляры: ф.19 (20170118) / Инвентарный номер: бр / Цена: 35.00 / Авт.знак: Г 95 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6